Porous-Coated Metaphyseal Sleeves in Revision Total Knee Arthroplasty: Midterm Results - Stefani, Giacomo; Mattiuzzo, Valerio; Prestini, Greta; Civitenga, Carolina; Calafiore, Roberto; Traverso, Francesco (Joints, 2019)
Purpose The aim of this study was to evaluate the efficacy in terms of clinical results and radiographic findings of using metaphyseal sleeves in revision total knee arthroplasty (TKA), and to check if the use of sleeves without stems did not impair such results.Methods In this retrospective study, 141 patients (143 knees) operated in the period 2008 to 2015 met the above-mentioned criteria and were invited to a medical examination including X-rays. A total of 121 knees were available for the study (44 in the group without stems and 77 in the group with stems). Mean follow-up was 63 months for the stemless group and 89 for the group with stems. Knee Society Score (KSS) (objective knee score) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were used as outcome scores and compared with baseline values, range of motion (ROM) was also compared with preop value and X-rays were also examined and compared with immediate postop X-rays to check signs of loosening and radiolucent lines, if any, and bone ingrowth. Satisfaction of the patients was also investigated using a linear scale from 1 to 10.Results KSS improved from 34 to 81 postop (39 to 81 in the stemless group) (p < 0.01), while WOMAC from 82% preop to 39% postop (76 to 37% in the stemless group) (p < 0.01). Forty-six patients were satisfied, 20 partially satisfied, and 11 unsatisfied (respectively 25–14–5 in the stemless group). ROM improved from 89 degrees preop to 99 degrees postop (93 to 98 degrees in the stemless group). X-rays showed no loosening of the implant, radiolucent lines in 8 patients, and bone ingrowth in 113 out of 121 patients.Conclusion In this midterm follow-up study, we found a significant improvement in clinical results compared with preop values. We found no difference between the two groups (with and without stems) thus suggesting that the use of stemless sleeves does not impair results in revision TKA.Level of Evidence Therapeutic case series, level IV.
Keywords: knee; total knee arthroplasty; revision; metaphyseal sleeves